2011
DOI: 10.1681/asn.2010090956
|View full text |Cite
|
Sign up to set email alerts
|

Suramin Inhibits Renal Fibrosis in Chronic Kidney Disease

Abstract: The activation of cytokine and growth factor receptors associates with the development and progression of renal fibrosis. Suramin is a compound that inhibits the interaction of several cytokines and growth factors with their receptors, but whether suramin inhibits the progression of renal fibrosis is unknown. Here, treatment of cultured renal interstitial fibroblasts with suramin inhibited their activation induced by TGF-␤1 and serum. In a mouse model of obstructive nephropathy, administration of a single dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 49 publications
(59 reference statements)
7
67
0
Order By: Relevance
“…30 A similar finding has been observed in UUO kidneys. 22 In support of this finding, we demonstrated that TbRII expression is significantly increased by UUO and that the treatment with 17AAG effectively prevents the enhancement of TbRII abundance.…”
Section: Hsp90 Inhibitor Reduces Renal Fibrosis H Noh Et Alsupporting
confidence: 75%
See 1 more Smart Citation
“…30 A similar finding has been observed in UUO kidneys. 22 In support of this finding, we demonstrated that TbRII expression is significantly increased by UUO and that the treatment with 17AAG effectively prevents the enhancement of TbRII abundance.…”
Section: Hsp90 Inhibitor Reduces Renal Fibrosis H Noh Et Alsupporting
confidence: 75%
“…4,5 Upregulation of TGF-b1 is a common finding in virtually every type of progressive chronic kidney disease, in both animals and humans. In cell culture systems, TGF-b1 stimulates mesangial cells, 21 interstitial fibroblasts, 22,23 and tubular epithelial cells 9,10,24 and induces matrix expression through its interaction with TGF-b receptors. Thus, TGF-b1 has been studied as a target to prevent the progression of renal fibrosis.…”
Section: Hsp90 Inhibitor Reduces Renal Fibrosis H Noh Et Almentioning
confidence: 99%
“…In a recent study, we found that suramin is effective in preventing the onset of renal fibrosis in a model of obstructive nephropathy when given immediately after surgical ligation of the ureter (Liu et al, 2011). In the present study, we further demonstrate that delayed administration of a single dose of suramin after UUO injury inhibits further increases in renal fibrosis as indicated by reduced deposition of ECM components and expression of type I collagen and fibronectin.…”
Section: Discussionsupporting
confidence: 78%
“…Here, we have shown that suramin is able to halt progressive renal fibrosis in a mouse model when given early after UUO injury. Our recent studies also show that suramin inhibited the progression of renal fibrosis and prevented renal function impairment in a rat model of remnant kidney disease (Liu et al, 2011). Therefore, suramin might be an interesting drug candidate for treating patients with CKD.…”
Section: Suramin Inhibits Progression Of Renal Fibrosis 763mentioning
confidence: 70%
See 1 more Smart Citation